Social Media Marketing in Shaping Behavioral Intentions (Study on the Influence of Social Media Marketing Content, Brand Trust, Brand Experience of Kahf Skincare on Behavioral Intentions of Instagram Followers @Kahfeveryday Through Relation Bonds) - Brenda Pranata; Hilarius Bambang Winarko (Asian Journal of Social and Humanities, 2023)
The realm of skincare, which was traditionally associated with women's needs, has undergone a significant shift where there is now an equal demand for skincare among men. The surge in demand for men's skincare products was particularly noticeable in the year 2020. This need was addressed by a renowned company, PT. Paragon Technology and Innovation, which innovatively launched a specialized brand for men's skincare called Kahf. Considering the current trend of utilizing social media for marketing purposes, the author was intrigued to examine how Kahf, as a specialized brand for men, carries out its marketing activities. Additionally, the study aims to explore the followers' response regarding their trust in using Kahf as their skincare choice, as well as their brand experience throughout the usage of the brand. These three variables are mediated by the presence of relational bonds to shape behavioral intentions. The research sample consists of 80 Instagram followers of @Kahfeveryday, and the data will be analyzed using the SmartPLS 3.0 measurement tool and bootstrapping technique. The research findings indicate that this men's facial skincare product exhibits a distinct treatment approach, differing in terms of the habits and strategies employed by the brand compared to the skincare marketing targeted towards women. It is crucial to construct an engaging narrative or storytelling that leverages current ongoing phenomena